Islamic Republic of Afghanistan : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context. Over the past decade, Afghanistan has made enormous progress in reconstruction, development and lifting per capita income. Security and political uncertainties, and weak institutions have constrained growth and weighed on social outcomes. With significant reform efforts and donor support, Afghanistan has maintained macroeconomic stability, implemented important structural reforms, and built policy buffers, but significant vulnerabilities remain. The IMF has been supporting Afghanistan through technical assistance and a three-year Extended Credit Facility (ECF) arrangement. Reviews under the ECF arrangement have been delayed. Outlook and risks. 2014 is a crucial year in the political and security transitions and the run-up to the 'transformation decade' (2015-24). Assuming smooth political and security transitions, continued reform and donor financing, the outlook should be positive. Large security and development expenditure needs and a limited domestic revenue capacity mean that Afghanistan will remain dependent on donor financing for an extended period. Macroeconomic stability, structural reforms, and political and security stability are needed to ensure inclusive growth. Risks, mostly on the downside, are related to adverse domestic or regional security developments, political instability, inadequate implementation of economic policies, and donor fatigue. Policy recommendations. The authorities' economic strategy (maintaining macroeconomic stability, strengthening the financial sector, improving economic governance, and moving toward fiscal sustainability) remains appropriate and needs strengthened implementation. Sustained implementation of this strategy will safeguard growth and build buffers to help manage shocks. Policies should continue to aim at strengthening revenue collection, managing money growth to control inflation while preserving exchange rate flexibility, strengthening bank supervision, and quickly enacting anti-money laundering (AML), countering financing of terrorism (CFT), banking, central bank, and value-added tax legislation.